Gastrointestinal Beriberi as a prodrome of non-alcoholic Wernicke’s encephalopathy: a study of an emerging nutritional deficiency disorder from Kashmir, India - Shah, Irfan Ahmad; Kawoos, Yuman; Shah, Asif Iqbal; Rabyang, Stanzen; Naqash, Henna; Mir, Mohd Rafi (International Journal of Research in Medical Sciences, 2019)
Background: Gastrointestinal manifestations of thiamine deficiency have not been well described in literature. Authors aimed to study the symptoms of gastrointestinal beriberi in a cohort of patients of non-alcoholic Wernicke’s encephalopathy and review the relevant literature. Methods: In a retrospective analysis, case records of 52 patients diagnosed with non-alcoholic Wernicke’s encephalopathy were analyzed for the nature of gastrointestinal symptoms, their duration, severity and associated findings, investigations and response to treatment. The available literature on gastrointestinal symptoms in thiamine deficiency disorders and gastrointestinal beriberi was reviewed. Results: Gastrointestinal symptoms were found in 46 of the 52 patients. The most common gastrointestinal symptom in our patients was recurrent vomiting in 42 patients. Eight patients had water brash. Ten patients had epigastric pain and 10 patients had anorexia. Based on the nature and severity of symptoms, patients were evaluated for their symptoms using endoscopy, ultrasonography, amylase and lactate levels, and routine laboratory studies and the results were normal in the majority of patients. Gastrointestinal symptoms settled in all the patients after receiving intravenous thiamine. On reviewing the literature multiple studies were found to have reported prominent gastrointestinal symptoms in patients of Wernickes encephalopathy and other thiamine deficiency related disorders. However, the definition of gastrointestinal beriberi is not clearly stated. Conclusions: Gastrointestinal symptoms were prominent prodromal manifestations in our cohort of Wernicke’s encephalopathy and have also been amply reported in literature. Presence of gastrointestinal symptoms in individuals predisposed to thiamine deficiency without alternative explanation should be enough to label a patient as gastrointestinal beriberi. The study highlights the importance of recognizing gastrointestinal beriberi as a distinct syndrome that may precede the development of Wernicke’s encephalopathy.